Teacher’s and Students’ Perspectives Regarding the Reading Materials in the Extensive Reading and Writing Class - Eunike Listyoyanti Suseno; Henny Putri Saking Wijaya (Institute of Research and Community Outreach - Petra Christian University, 2021)
This qualitative study aimed to know the teacher’s and the students’ perspectives regarding the reading materials in the Extensive Reading and Writing (ERW) class. The study used the theory of Extensive Reading Principles by Day and Bamford (2002). The study also tried to draw the similarities and differences between their perspectives. The subjects of the research were 10 students and 1 teacher from ERW class in the English Department of Petra Christian University, Surabaya. Semi structured interviews were used to explore their perspectives toward the reading materials of ER. The findings showed that the teacher and the students had various perspectives regarding the reading materials in ERW class. In conclusion, the provision of reading material was not really in line with the ER principles because of the unique nature of ERW class. For the future research, the writers suggested doing quantitative research with a variety of subjects for more generalizable result. Keywords: extensive reading, implementation, perspectives, students, teachers